Detection of Bacteria in Water with β-Galactosidase-Coated Magnetic Nanoparticles. (December 2018) - Cui, Mingyue; Chang, Hao; Zhong, Yang; Wang, Min; Wu, Tianze; Hu, Xiao; Xu, Zhichuan J.; Xu, Chenjie
Pathogenic contamination and resistant bacterial infections remain critical concerns in both developed and developing countries. Rapid and sensitive detection of pathogens is still a key requirement for both environmental and clinical settings. This article introduces a simple, colorimetric, cost-effective, and high-throughput system based on a positively charged iron oxide/enzyme complex for the detection of both gram-positive and gram-negative bacteria in water between 10 3 and 10 8 cfu/mL. This study provides an effective strategy for the identification and purification of pathogen contamination in drinking water.